Does ABO incompatibility matter?. Issue 10 (October 1988) - Quinn, M W; Weindling, A M; Davidson, D C
Abstract : The incidence and severity (peak serum bilirubin concentration) of clinically detectable jaundice was determined retrospectively in 110 elution positive cases of ABO incompatibility. Neither the incidence nor the severity of jaundice in the study group differed significantly from a control group. In the individual case Coombs positivity and/or a strongly positive elution test may be a helpful predictor of jaundice occurring but not of its severity.